Psychological Factors Affecting the Incidence of Essential Hypertension in General Hospital of Makassar - Yonathan Ramba; Suharto Suharto; M. Bagus Qomaruddin; Dewi Retno Suminar; Hendrik Hendrik (Humanistic Network for Science and Technology (HNST), 2018)
The problem with patients with essential hypertension is that they do not know the cause of their illness, so they do not know how to overcome them. In addition, many hypertensive patients who have not received the proper treatment, if they have received treatment, but their blood pressure has not dropped as expected. The purpose of the study is to analyze the psychological factors that influence the occurrence of essential hypertension. This study was an observational study with a cross-sectional design by looking at the influence of psychological factors on the occurrence of essential hypertension. The study population was essential hypertensive patients who seek treatment at Daya General Hospital. Samples were essential hypertensive patients, aged 20-70 years, minimal education of primary schools and domiciled in Makassar which were obtained by non-probability sampling so that the sample size was 53. Data collection techniques through blood pressure measurement and questionnaire. ANOVA multiple comparison results showed that anger, depression, and mood had a significant effect on the incidence of essential blood pressure (p-value ˂ 0.05). Keywords: Essential hypertension, Anxiety, Anger, Hostility, Depression, Mood